a. M, The mass of the moon is 7.35x10^{22}kg

r, The radius of the moon is 1.74x10^{6}m

G is the universal gravitational constant G=6.674x10^{-11}m^{3}kg^{-1}s^{-2}

g=GM/r^{2}=(6.674x10^{-11}m^{3}kg^{-1}s^{-2}*7.35x10^{22}kg)/(1.74x10^{6}m)^{2}=1.62m/s^{2}

**g**_{moon}**=1.62m/s**^{2}

b. M, The mass of Venus is 4.88x10^{24}kg

r, The radius of Venus is 6.06x10^{6}m

G is the universal gravitational constant G=6.674x10^{-11}m^{3}kg^{-1}s^{-2}

g=GM/r^{2}=(6.674x10^{-11}m^{3}kg^{-1}s^{-2}*4.88x10^{24}kg)/(6.06x10^{6}m)^{2}=8.87m/s^{2}

**g**_{Venus}**=8.87m/s**^{2}